Towards photovoltaic windows: scalable fabrication of semitransparent modules based on non-fullerene acceptors via laser-patterning. Issue 19 (11th May 2020) - Pascual-San-José, Enrique; Sadoughi, Golnaz; Lucera, Luca; Stella, Marco; Martínez-Ferrero, Eugenia; Morse, Graham Edward; Campoy-Quiles, Mariano; Burgués-Ceballos, Ignasi
Abstract : We use state-of-the-art absorbing materials and industrially compatible processing techniques and conditions to fabricate semitransparent organic photovoltaic (OPV) module prototypes that exceed 30% transparency. Abstract : Semitransparent organic photovoltaics (OPV) possess unique properties that make them highly appealing for their integration into semitransparent architectonic elements such as windows or glazings. In order to provide sufficient transparency, non-opaque electrodes and thin photoactive layers are typically used, thus limiting the light-harvesting capacity. This can be partially overcome by using materials that absorb light mostly in the infrared region. On the other hand, the use of scalable techniques for the fabrication of semitransparent devices is often disregarded. In this work, we combine the blue, low-bandgap polymer PBTZT-stat-BDTT-8 with the near-infrared absorbing non-fullerene acceptor 4TICO, adapting the module fabrication to low-cost manufacturing processes that are compatible with large-scale production. Fully solution-processed semitransparent solar cells over 4.7% performance are prepared from non-chlorinated formulations, in air and using scalable techniques such as blade coating. Our prototypes of semitransparent laser-patterned OPV modules exceed 30% of transparency (measured as human perception transmittance, HPT) and yield efficiencies in the range of 4%, geometrical fill factors surpassing 90% and an active area above 1 cm 2 . We verify the quality of cell-to-cell interconnection and optimise the geometry of the modules with the help of local optoelectronic imaging techniques. This work highlights the relevance of non-fullerene acceptors with strong absorption in the near-infrared, as they can meet industrial and technical requirements for the upscaling and integration of high-performance semitransparent OPV modules with low production costs.